Start-up A Practical Guide to Starting and Running a New Business - Harris, Tom.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
So your dream is to start your own business. But how do you know if it will work and how do you make it a reality? Start-up is a user guide for aspiring entrepreneurs and provides expert advice and guidance on every aspect of launching a new business. It will be of particular value if you are an academic wishing to exploit the commercial value of a new technology or business solution through the creation of a new company. Step-by-step, this inspiring and highly readable book covers how to evaluate the strength of your business idea, how to protect your invention, what legal steps and responsibilities are involved in forming a company, how to position your products in the market, how to create a business plan and raise finance. The case studies, practical exercises and tips in this book will help to demystify the process of starting a new business, give you the confidence to do it and greatly increase your chances of realising your dream.
How good is your idea? -- How can you protect your ideas? -- What is a company? -- How do you market your product? -- How do you finance your business? -- How do you create a financial model? -- How do you write a business plan? -- Your role and your team -- Closing remarks.
Keywords: Entrepreneurship; Engineering—Vocational guidance; Computers; Management; Marketing; Entrepreneurship; Job Careers in Science and Engineering; The Computing Profession; Management; Marketing